Tanggung Jawab Pelaku Usaha Terhadap Konsumen Dalam Promo Flash Sale Pada Marketplace Shopee - Alwinda Oktarie; Firdaus Firdaus; Rahmad Hendra (Jurnal Ilmiah Wahana Pendidikan, 2023)
Flashsale is a sales promotion strategy carried out by retailers in the online and offline world, including the Shopee marketplace. The rise of fraud committed by business actors in Shopee flashsale promos using flashsale opportunities has often occurred, this of course makes Shopee consumers feel disadvantaged and disappointed because the long-awaited Flashsale does not match the advertised and promoted goods, impacting Shopee marketplace sellers by reduced consumer interest in participating in the next Flashsale promo. This type of research is sociological juridical. The location of this research is in the jurisdiction of Pekanbaru City. This research was conducted by means of interviews, and literature review. The results of the study are, the actions of business actors regarding the number of products and prices listed in flashsale promos that are not in accordance with what is stipulated in the consumer protection law, can be said to be bad faith from business actors in running a business and not complying with the corridors of obligations of business actors which is regulated in point a of Article 10 of Law Number 8 of 1999. In the absence of system improvements with available item data cases, consumers feel distrusted and lead to losses for the business actors themselves. There is a need for a thorough improvement in the system and education about regulations and the consequences of violations to the community